We're Not Afraid of Cancer or Prevention as a Doorway to Health Oncological Prevention Methology for Lower Secondary Schools - Slaná Reissmannová, Jitka (Masaryk University Press, 2020)
Methodological material "We're not afraid of cancer or prevention as a doorway to health" is focused on the prevention of oncological diseases and it is intended for teachers of upper primary schools for teaching Health Education, eventually Biology. Cancer is nowadays one of the most common diseases. The prevention plays important role in decreasing the incidence of oncological diseases, therefore it is very important that the basic knowledge about prevention of oncological diseases to be given to primary school pupils. The main purpose is to acquaint pupils with primary and secondary prevention of oncological diseases and to increase their health literacy in this area. The material includes suggestion of 10 lessons. Each of them contains professional information for teachers' theoretical preparation, suggestion of the lesson, a worksheet with solution and proposal activities on the topic.